The Institutional Settings of the Recovery of the NGO Sector in Post-Communist Countries - Halina Waniak-Michalak; Ivana Perica; Sviesa Leitoniene; Ewa Chojnacka (Comparative Economic Research. Central and Eastern Europe, 2020)
The purpose of the paper is to describe the process of creating institutional settings in three post-communist countries and analyze the change of the social trust in these countries in line with the development of legal and accounting rules and norms for NGOs. The design and methodology include a literature analysis and the inductive method to analyze historical data for each country. The countries that were selected for the research are Lithuania - one of the Baltic states, which is in the last place in the World Giving Index (WGI) ranking, Poland with the average result in WGI ranking, and Croatia - the best post-communist country in the WGI ranking. Research limitations include the use of the descriptive method and the small number of countries included in the analysis. The originality and value of this paper lie in the fact that the problem of low social trust in NGOs in post-communist countries is analyzed by linking it with the development of NGO accountability and civil control over them.
Keywords: M41; I31; 330; NGOs; post-communist countries; institutional theory; NGOsaccountability; civil trust